Experience Marketing Backstage: The View of the Managers in the Application of Branding Strategies Through Actions of Sponsorship and Development of Projects and Events - Cerqueira, Alana Vitória Lacerda; Lopes, Evandro Luiz; da Silva, Jussara Goulart (Future Studies Research Journal: Trends and Strategies, 2019)
The research aimed to understand how organizations adopt experience marketing practices, seeking to explore the backstage of projects and events. This is a qualitative study conducted through interviews with four managers of large organizations. As a result, it has been achieved that experience marketing management through the five categories experience, projects and events, drivers and priorities, budgets and results and decision factors seeks to meet human yearnings by positioning values, causes and emotions. For future studies, it is suggested to analyze how consumers receive the repercussion of the experiential message through digital content.